Armazenamento e vigor de sementes de Stylosanthes capitata vog. - CASTRO, CARLOS RENATO TAVARES DE; ALVARENGA, EVELINE MANTOVANI; SILVA, ROBERTO FERREIRA DA; REIS, FERNANDO PINHEIRO; REIS, MÚCIO SILVA (Revista Ceres, 2015)
.